sICAM-1 intrathecal synthesis and release during the acute phase in children suffering from Coxsackie A9 and S. pneumoniae meningoencephalitis Sintesis intratecal de sICAM-1 y liberación durante la fase aguda en niños con meningoencefalitis por Coxsackie A9 y S pneumoniae - Alberto J. Dorta-Contreras; Piotr Lewczuk; Bárbara Padilla-Docal; Elena Noris-García; Raisa Bu Coifiu-Fanego; Consuelo Sánchez-Martínez; Alexis Rodríguez-Rey; Marlén González-Hernández (Arquivos de Neuro-Psiquiatria, 2008)
The intercellular adhesion molecule is a transmembrane glycoprotein belonging to the immunoglobulin superfamily. Serum and cerebrospinal fluid (CSF) soluble intercellular adhesion molecule 1 (sICAM-1) from normal control children as well as from children with Guillain-Barré syndrome (GBS), with Coxsackie A9 virus meningoencephalitis and with Streptococcus pneumoniae meningoencephalitis were studied. sICAM-1 was quantified using an immunoenzimatic assay and albumin using the immunodiffusion technique in both biological fluids. Increased sICAM-1 values in CSF in patients with GBS correspond to an increase of the albumin CSF/serum quotient. In contrast, in inflammatory diseases like S. pneumoniae and Coxsackie A9 virus meningoencephalitis an increased brain-derived fraction was observed. In particular cases these values are 60-65% and 70-75% respectively. The results indicate an additional synthesis of sICAM-1 in subarachnoidal space during central nervous system (CNS) inflammatory process. An important role of sICAM-1 in the transmigration of different cell types into CSF during CNS inflammation in children with S. pneumoniae and Coxsackie A9 meningoencephalitis may be suggested. La molécula de adhesión intercelular es una glicoproteína que pertenece a la superfamilia de las inmunoglobulinas. Se estudiaron los niveles de molécula de adhesión intercelular tipo 1 soluble (sICAM-1) en suero y líquido cefalorraquídeo (LCR) de niños con meningoencefalitis por Streptococcus pneumoniae y por Coxsackie A9 al igual que en niños con sindrome de Guillain-Barré (SGB). sICAM-1 fue cuantificado por ensayo inmunoenzimático y la albúmina por inmunodifusión en ambos líquidos biológicos. Los valores incrementados de sICAM-1 en LCR en los pacientes con GBS corresponden a valores aumentados de razón LCR/suero de albúmina. En contraste, en las enfermedades inflamatorias como las meningoencefalitis por S. pneumoniae y por Coxsackie A9 se observa un incremento en la fracción derivada del cerebro. En casos particulares los valores se incrementan hasta un 60-65% y 70-75% respectivamente. Los resultados indican una síntesis adicional de sICAM-1 en el espacio subaracnoideo durante el proceso inflamatorio del sistema nervioso central (SNC). Esto puede sugerir un importante papel del sICAM-1 en la transmigración de diferentes tipos celulares en el LCR durante la inflamación del SNC en niños con meningoencefalitis por S pneumoniae y coxsackie A9.